(untitled) (Modern education and development, 2025)
Theoretical aspects of training for the development of the agricultural sector are covered. The search for and implementation of new approaches, models and methods for the development of the agricultural sector is described in detail. The factors influencing the training of personnel for the development of the agricultural sector were studied.